Transitioning a cardiovascular health and rehabilitation programme to a virtual platform during covid 19. (29th July 2021) - Mcgaffin, S; Taggart, M; Smyth, D; O"doherty, D; Brown, J; Teague, S; Slevin, C; Montgomery, L; Coll, M; Lindsay, C; Crumley, B; Gibson, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Our Hearts Our Minds Purpose: Can a virtual cardiovascular prevention and rehabilitation programme be as effective as face-to-face programme. Background: The Our Hearts Our Minds (OHOM) prevention and rehabilitation programme rapidly transitioned to a virtual platform in the covid era.  Here we compare if a virtual programme potentially could offer the same standard of the nursing intervention (education, smoking cessation, medical risk factor management and psychosocial health) as the previous face to face programme Methods: Both the initial assessment (IA) and end of programme (EOP) assessments were conducted via telephone/video as per patient preference. The following measures were recorded at both time points (home blood pressure (BP) monitors were provided) Smoking (self report) BP/Heart rate, Lipids/HbA1c (facilitated by phlebotomy hub), cardio protective drugs (doses, adherence), Hospital Anxiety and Depression score, EuroQoL Nursing Intervention Smoking cessation counselling and pharmacotherapy where appropriate Weekly meeting with cardiologist to optimise BP and lipid management and up titration cardio protective drugs Bimonthly virtual coaching consultation for monitoring/goal resetting Bimonthly group video education sessions Results: From April to November 2020, of the 432 referrals received 400 were eligible with 377 accepting the offer of an IA (94% response rate). 262 have had an IA with the remaining 115 awaiting an assessment date.  Of the completed IA's 257 were willing to attend the programme (98% uptake).  120 had been offered an end of programme assessment with 114 attending (96% of those offered). The results for the virtual programme were then compared to the same period one year previously when the programme was fully face to face and are outlined in the table below. The comparison of results delivered via remote delivery are remarkably similar to those achieved in the previous year delivered via face to face. Conclusion: Initial data has shown that virtual delivery of the nursing component of the OHOM prevention/rehabilitation programme was highly acceptable to patients and was as effective as that of the traditional face to face service. Table 1 below exhibits the clinical and patient-reported outcomes.